The Characteristic Findings of Sacroiliitis Using Magnetic Resonance Imaging in Patients with Axial Spondylarthritis and Brucellosis - Yolbas, Servet; Bozgeyik, Zulkif; Denk, Affan; Yildirim, Ahmet; Koca, Suleyman Serdar (Clinical & Exper Rheumatology, 2014)
[Abstract Not Available]
Keywords: sacroiliitis; axial spondylarthritis; brucellosis